Empirical Model Of Shear Force Capacity And Stiffness Of Shear-Tension Screw Connections In Timber-Concrete Composite Structures - Ghazali, Anis Hanim (Universiti Sains Malaysia, 2022)
Timber-concrete composite (TCC) systems are a construction technique used in rehabilitation works of existing timber floors and for new construction such as multistory buildings and short-span bridges. The system combines high tensile strength of timber beams and high compressive strength of concrete slabs, which act compositely together. Therefore, adequate mechanical performance to these composite structures must be assured using shear connectors characterized by sufficient resistance and stiffness. This research study will evaluate the effect of different formations of screw connections, mainly in shear-tension formation and shear-compression formation. The effect of screw connection on shear-tension and shear-compression will be analyzed by plotting the shear force capacity and stiffness graph against the known parameters. The R-squared value related to the trendline will be displayed on the graphs to interpret the data. The value of R2 greater than 0.5 indicates that the dependent variable highly influenced the independent variable. In this paper, a new empirical model to calculate the shear force capacity and stiffness of timber-concrete composite (TCC) joints made with inclined screws, specifically in shear-tension is proposed and compared to models derived by Gelfi et al. (2002), Moshiri et al. (2014), and Symons et al. (2010). The models will be compared based on their mean, standard deviation, coefficient of variance, and regression value. A comparison between the new proposed model with the other models is reported and critically discussed in terms of both shear force capacity and stiffness. It was observed that the new empirical model of the shear force capacity and stiffness has R2 values of 0.9364 and 0.5118, respectively. The value of R2 obtained from plots of both empirical models was higher than that obtained from other model plots. The finding indicates that the new empirical model can better predict shear force capacity and stiffness in TCC connection.